Promoting agroforestry in Rwanda: The effects of policy interventions derived from the theory of planned behaviour - Beatrice Noeldeke (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2022)
Although agroforestry offers multiple benefits, its adoption by small-scale farmers remains low in some regions in developing countries. Besides economic motives also intrinsic motivations can influence farmers' behaviour. This study identifies farmers' intrinsic drivers to adopt agroforestry based on the Theory of Planned Behaviour. Furthermore, it compares policy instruments which address the intrinsic drivers to promote agroforestry adoption. Specifically, an agent-based simulation model investigates whether the following interventions increase adoption intentions 1) an information campaign to spread awareness of agroforestry benefits to strengthen positive attitudes, 2) informing farmers about social norms to reinforce their perception of subjective norm, and 3) providing trainings to improve farmers' perceived behavioural control. The research is applied to a case study in rural Rwanda. In line with the Theory of Planned Behaviour, a partial least squares structural equation model confirms that attitude, subjective norm, and perceived behavioural control influence farmers' adoption intention. The simulations demonstrate that all interventions significantly increase farmers' intention to adopt agroforestry, but their effectiveness is rather small. The information campaign targeting attitude causes the strongest increase. The relatively weak effectiveness of the individual interventions can be enhanced by their combined implementation. Policy-makers who aim to raise low agroforestry adoption rates should consider strategies that target intrinsic drivers as alternatives to economic incentives.
Keywords: O13; O21; Q18; 330; Agroforestry; Innovation Adoption; Theory of Planned Behaviour; Policy Interventions; Small-scale Farming